1992
DOI: 10.1111/j.1532-5415.1992.tb02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Status among the Homebound Elderly: An Epidemiologic Perspective

Abstract: Objective To compare the prevalence of specific psychiatric disorders in the homebound elderly to other elders, controlling for demographic, physical health, and socio‐economic factors. Design Survey. Setting Epidemiologic Catchment Area (ECA) project in New Haven, CT. Participants 2,553 non‐institutionalized elders representing the total elderly population of the greater New Haven area. Intervention None Main Measures Homebound status determined by self‐report; psychiatric status according to DSM III by the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 18 publications
4
61
0
1
Order By: Relevance
“…Demographic, physical, medical, and psychological factors previously associated with the frequency of going outdoors, independent of mobility or functional status were included in the current study, specifically age, sex, chronic medical conditions, 2,22,23 impairments of vision and hearing, 3,22 urinary incontinence, 3,24-26 subjective health, 2 depressive mood state 2,23 and cognitive function. 4 We ascertained the presence of chronic conditions (defined as a history of physician-diagnosed heart disease, stroke or diabetes mellitus) from the subject's report.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Demographic, physical, medical, and psychological factors previously associated with the frequency of going outdoors, independent of mobility or functional status were included in the current study, specifically age, sex, chronic medical conditions, 2,22,23 impairments of vision and hearing, 3,22 urinary incontinence, 3,24-26 subjective health, 2 depressive mood state 2,23 and cognitive function. 4 We ascertained the presence of chronic conditions (defined as a history of physician-diagnosed heart disease, stroke or diabetes mellitus) from the subject's report.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…A depression screening day planned for a possible 4500 older people resulted in only two people attending (Forbes et al, 1995), while Ilie et al (1994) found that opportunistic screening for depression by general practitioners did not alter their clinical practice. Secondly, screening instruments used only with surgery attenders will miss depression among groups at particular risk, such as the homebound elderly (Bruce and McNamara, 1992). Thirdly, as part of a wider domiciliary health check, physical and social problems can be considered alongside mental health problems more easily than in a general practice consulting room.…”
mentioning
confidence: 99%
“…for the PHQ-2 variable and 227,283 for the Medicare Claims variable) subjects, the PHQ-2 determined that 15,473 (7.0% of the sample) were depressed, and the Medicare Claims determined that 27,249 (12.0% of the sample) were depressed. The resulting depression percentages fell within the ranges of depression that have been found with homebound older adults (Bruce & McNamara, 1992;Choi & McDougall, 2007;Choi et al, 2010;Qiu et al, 2010). The demographics of the PHQ-2 and Medicare Claims samples vary a bit depending on the variables used in each analysis.…”
Section: Methodsmentioning
confidence: 71%
“…Although both of these measures have issues, the resulting depression percentages fall within the ranges of depression that have been found with homebound older adults (Bruce & McNamara, 1992;Choi & McDougall, 2007;Choi et al, 2010;Qiu et al, 2010). A crosstab analysis between the two depression measures used in the present study revealed that of the 219,883 subjects without missing data in either depression variable, 180,715 (82.2%) were determined by both samples to not be depressed and 1,872 (0.01%) were determined by both samples to be depressed.…”
Section: Sample and Methodological Issuesmentioning
confidence: 92%
See 1 more Smart Citation